Antibiotic Consumption 2017-2022 in 30 Private Hospitals in France: Impact of Antimicrobial Stewardship Tools and COVID-19 Pandemic - Pierre-Marie Roger; Diane Lesselingue; Anouk Gérard; Jacques Roghi; Pauline Quint; Sophie Un; Agnès Chincholle; Assi Assi; Odile Bouchard; Véronique Javaudin; Eric Denes (MDPI AG, 2024)
Our aim was to determine the impact of antimicrobial stewardship tools (ASTs) and the COVID-19 pandemic on antibiotic consumption (AC). We used the national software Consores® to determine AC in DDD/1000 days of hospitalization from 2017 to 2022 in voluntary private hospitals in France. The ASTs considered were: 1. internal guidelines; 2. the list of antibiotics with restricted access; 3. the presence of an antibiotic referent or 4. an ID specialist; and 5. proof of an annual meeting on antimicrobial resistance. Institutions with dedicated units for COVID-19 patients were specified. In 30 institutions, the total AC varied from (means) 390 to 405 DDD/1000 DH from 2017 to 2022. Fluoroquinolones and amoxicillin/clavulanate consumption decreased from 50 to 36 (p = 0.003) and from 112 to 77 (p = 0.025), respectively, but consumption of piperacillin/tazobactam increased from 9 to 21 (p < 0.001). Over the study period, 10 institutions with ≤2 AST had lower AC compared to 20 institutions with ≥3 AST (p < 0.01). COVID-19 units opened in 10 institutions were associated with a trend toward higher macrolide consumption from 15 to 25 from 2017 to 2020 (p = 0.065) and with an acceleration of piperacillin/tazobactam consumption from 2020 to 2022 (p ≤ 0.003). Antibiotic consumption in 30 private hospitals in France was inversely related to the number of AST. The COVID-19 pandemic was associated with limited impact on AC, but special attention should be paid to piperacillin/tazobactam consumption.